Accuracy of a heart rate monitor for calculating heart rate variability parameters in exercising horses - Frippiat, T.; van Beckhoven, C.; Moyse, E.; Art, T. (Journal of Equine Veterinary Science, 2021)
Heart rate is evaluated in exercising horses to monitor the level of fitness to exercise, and it is usually acquired using heart rate monitors (HRM) or telemetric electrocardiograms (ECG). While HRM are commonly available and easy-to-use for horse's owners, ECG is a more expensive equipment requiring user's experience. Interest for heart rate variability (HRV) in horses is increasing for both research and clinical purposes. HRV is usually calculated from interbeat intervals (IBI) obtained by ECG. The aim of this study was to determine the accuracy of an HRM to detect IBI for the calculation of HRV in both resting and exercising horses. Simultaneous ECG and HRM recordings were performed on 13 horses and ponies under normal training conditions for at least 45 minutes. IBI from ECG were corrected using a dedicated software. IBI from HRM were exported without correction. Two HRV-parameters were calculated on both recordings for resting and exercising periods: the standard deviation of R-R intervals (SDRR) and the root mean square of successive differences (RMSSD). Agreement and concordance between the two systems were determined using Bland-Altman plot and Lin's correlation coefficient, respectively. Effects of variables were consequently assessed. For both HRV-parameters during resting and exercising periods, the means of the differences between the two systems were lower than 0.47 ms with a correlation coefficient higher than 0.999. Height, weight and body condition score had no effect on the results. The studied HRM could be of interest as easy-to-use device for obtaining HRV-parameters SDRR and RMSSD in resting and exercising horses.